Antécédents familiaux et connaissance de l’anglais chez les francophones du Québec : family background and the knowledge of English by Quebec francophones - Vaillancourt, François; Lefebvre, Lise (L'Actualité économique)

(untitled) (HEC Montréal, 1981)
ABSTRACTThis paper examines, using the human capital framework, the relationship between family background and the knowledge of English by Quebec francophones. Using the Probit method and 1978 data we find that the level of schooling and the mother tongue of both father and mother, the occupation of the father and his ethnic origin, the sex of the individual and where he was born, all have an impact on the likelihood of knowing English.